(untitled) (Research, Society and Development, 2022)
Fractures of the Zygomatic-Maxillary Complex (CZM) are considered one of the most common fractures of the facial region, due to their projection from the bones that make up this region. They represent about 25% of all facial fractures and are usually the result of industrial accidents, sports injuries and interpersonal fights. This study aims to review the literature on fractures of the zygomatic complex, emphasizing its diagnosis, surgical protocol and possible complications after operative treatment. For the construction of this article, a bibliographic survey was carried out in the SciVerse Scopus, Scientific Electronic Library Online (Scielo), Virtual Health Library (BVS) and U.S. National Library of Medicine (PUBMED). Articles from the years 2000 to 2022 were selected. From the literary search, 22 articles were included in the present study. The management of zygomatic fractures remains a challenge and controversies persist. New technologies and approaches may ultimately allow for more accurate correction of fractures when using less invasive or less visible access. The surgeon must carefully evaluate the different tools and strategies available to provide patients with surgical options that provide the most stable and accurate reduction while also minimizing iatrogenic morbidity.